IMPROVING STUDENTS ABILITY BY USING ALIBI GAME - Antoni, Wili; Apriliaswati, Rahayu; ., Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research are to find out how the alibi game improve students’ speaking ability, to see whether this technique can be applied in class room activity to solve students’ problem and to see whether this technique can apply in class room activity to solve students’ problem in using chronological event in oral recount text. This classroom action research was conducted in three cycles, where each cycle consists of four stages of planning, acting, observing and reflecting. The result of the research proved that alibi game helped students speaking ability especially in telling recount. Alibi game has 3 parts that help students’ problems in oral recount. They are discussion, interrogation and conclusion parts. The process of the game requires students to tell in past tense which is the language feature of recount. Keyword: alibi game, Recount Abstrak: tujuan penelitian ini adalah untuk menemukan bahwa permainan alibi mengembangkan kemampuan berbicara siswa, untuk melihat apakah teknik ini bisa di aplikasikan di ruang kelas untuk menyelesaikan masalah siswa dalam menggunakan kejadian kronologi dalam recount teks lisan. Penelitian tindakan kelas ini di selesaikan dalam tiga lingkaran dimana setiap lingkaran terdiri dari perencanaan, peranan, penelitian dan refleksi. Hasil penelitian membuktikan bahwa permainan alibi membantu kemampuan berbicara siswa terutama menceritakan cerita. Permainan alibi memiliki tiga bagian yang membantu siswa dalam recount secara lisan. Mereka adalah, bagian diskusi, interogasi dan konklusi. Proses dari permainan ini mengharuskan siswa untuk bercerita menggunakan simple past tense yang mana adalah sifat bahasa dari recount. Kata kunci: Permainan alibi, Recount